2018
DOI: 10.1186/s13098-018-0375-9
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic fat deposition is increased and related to beta-cell function in women with familial partial lipodystrophy

Abstract: BackgroundTo study pancreatic fat deposition and beta-cell function in familial partial lipodystrophy (FPLD) patients.MethodsIn a cross-sectional study, eleven patients with FPLD, and eight healthy volunteers were matched for age and body mass index and studied at a referral center. Body composition was assessed using dual-energy X-ray absorptiometry and the Dixon method of magnetic resonance imaging was used to quantify pancreatic and liver fat. Fasting plasma glucose, insulin, leptin, lipids and homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…FCS is by nature a genetically determined model of partial lipodystrophy, covering a wide range of phenotypes including underweight patients presenting abnormally low skin folds an almost complete absence of subcutaneous adipose tissue [ 36 ]. Partial or complete lipodystrophy has also been associated with an increased pancreatic fat content [ 37 ], thus conferring a pro-inflammatory environment at the pancreas immediate vicinity. Accordingly, intrapancreatic fat (non-alcoholic fatty pancreas disease, NAFPD) has been identified as an independent correlate of acute pancreatitis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…FCS is by nature a genetically determined model of partial lipodystrophy, covering a wide range of phenotypes including underweight patients presenting abnormally low skin folds an almost complete absence of subcutaneous adipose tissue [ 36 ]. Partial or complete lipodystrophy has also been associated with an increased pancreatic fat content [ 37 ], thus conferring a pro-inflammatory environment at the pancreas immediate vicinity. Accordingly, intrapancreatic fat (non-alcoholic fatty pancreas disease, NAFPD) has been identified as an independent correlate of acute pancreatitis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It explains, for example, the metabolic pattern usually observed in patients with lipodystrophies. These genetic diseases are characterized by different degrees of incapacity to expand subcutaneous adipose tissue (SAT) and increased ectopic fat in muscle [28], liver [29] and pancreas [30]. Consequently, patients with lipodystrophies have severe IR, which can lead to MetS, NAFLD and diabetes.…”
Section: Pathogenesismentioning
confidence: 99%
“…Approximately 85% of total adipose tissue mass in healthy individuals is in the subcutaneous compartment, reflecting its importance as a major site of energy storage [ 24 ]. In lipodystrophies, the loss of subcutaneous white adipose tissue is associated with free fatty acid metabolism dysregulated in visceral adipose tissue and increased deposition in liver, pancreas and muscle, and endothelial dysfunction [ 4 , 25 27 ]. Independent of VAT or upper body fat depot, studies have shown that increased lower body fat particularly gluteofemoral fat, is independently associated with reduced cardiovascular risk, and conversely, reduced lower body fat is associated with increased cardiovascular risk [ 4 , 21 , 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%